Factors that Influence Regional Original Income in Gunungkidul Regency - Adila Eka Widianti; Rigel Nurul Fathah; Seto Bayu Bayu Aji (Proceeding International Conference on Accounting and Finance, 2025)
This study aims to analyze the factors affecting Local Own-Source Revenue (Pendapatan Asli Daerah) in Gunungkidul Regency. The data used in this research is secondary data in the form of time series data from 2018 to 2022, and the sample consists of 24 tourist attractions in Gunungkidul Regency obtained from the Central Statistics Agency (Badan Pusat Statistik). This study employs regression model selection, including the Common Effect Model (CEM) test, Multicollinearity test, Heteroscedasticity test, Regression Model, and F-test. The results of the study show that the variable PBB-P2 contribution level significantly affects Local Own-Source Revenue. The study also indicates that the variable PBB-P2 growth rate has a significant influence on Local Own-Source Revenue, as shown by the statistical result with a probability value (PROB) of 0.000. Meanwhile, the tourism retribution variable shows no effect on Local Own-Source Revenue, as indicated by the regression coefficient of -0.006. Furthermore, the tourist visit variable also does not affect Local Own-Source Revenue, as seen from the regression test results showing a probability value of tourist visits (0.299 > 0.000).